A History of Western Society from the age of exploration to the present : volume 2 - Wiesner, Merry E.; Crowston, Clare Haru; Perry, Joe; MacKay, John P. (Bedford/Saint Martin's, 2022)
A lively journey through the story of Western civilization, focusing on societies, cultures, and the lives of both ordinary and extraordinary men and women.